Neutrophil-to-Lymphocyte Ratio (NLR) as a Marker of CKD Progression in T2DM Patients - Shruthi, J.; Kumar.S, Suresh; R, Kulothungan. (Journal of Neonatal Surgery, 2025)
Background: The neutrophil-to-lymphocyte ratio (NLR), a simple marker of systemic inflammation, has been recognized for its potential role in chronic disease states. This study investigates the association between NLR and chronic kidney disease (CKD) in patients with type 2 diabetes mellitus (T2DM) in a tertiary care centre in Chengalpattu, India. Methods: A cross-sectional study was conducted among 150 T2DM patients attending the nephrology and endocrinology OPD. CKD was staged using eGFR and albuminuria levels according to KDIGO guidelines. NLR was calculated from complete blood count values. The association between NLR and CKD stages was evaluated using statistical tools. Results: A significant increase in NLR was observed with advancing CKD stages (p < 0.001). Positive correlation was found between NLR and albuminuria and a negative correlation was found between NLR and eGFR. ROC curve analysis demonstrated an NLR cut-off of 2.8 to predict advanced CKD (stage 3 and above) with a sensitivity of 78% and specificity of 72%. Conclusion: Elevated NLR is significantly associated with CKD progression among T2DM patients and may serve as a cost-effective, accessible marker for early risk stratification.